Reassentamento e integração local: as limitações institucionais e de políticas em relação aos refugiados palestinos em São Paulo - Rodrigues, Viviane Mozine (2015)
Geographically divided in two states, São Paulo and Rio Grande do Sul, in 2007 Brazil received 108 Palestinians from a refugee campsite in Rweished, Jordan, through the Brazilian solidarity resettlement program. For this thesis, the spatial area of the subjects is focused on the refugee group resettled at Mogi das Cruzes, São Paulo. Generally, this study pursuits to present the Brazilian context in resettlement of Palestinians and their local integration, enlightening institutional limitations (government agencies, of civil society and the international community) and policies (internal and international legislations and public policy), therefore using an transdisciplinary approach from Political Science, International Relations, Sociology, History, Geography and Law. The resettlement and the local integration are two durable solutions to the UNHCR, meaning, they are two more lastingly, perhaps permanent solutions to the issue of refuge in cases which return to the country of origins is out of question. The issue presented with the Palestinians is that the resettlement was not followed by a local integration of the group, reason why it was marked by tensions and protests concluding with the diminish of the Brazilian quota granted to the resettlement program and, at least temporarily, the negative perception of Palestinians refugees in the same program. To investigate the answer to this question, interviews were conducted which allowed us a general characterization of the Palestinians refugees resettled and also the opinions of institutions that deal directly with the refuge matter. Brazil is a country that host refugees showing great solidarity, however the great contradiction is this solidarity in incomplete or restricted, because it does not automatically inserts these groups in its social policies, depriving them of economic, cultural and social rights. What we attain is that the action of the Brazilian State in favor of the refugees is still insufficient, resulting in the local integration being very dependent on the interaction of the civil society. However, if in one hand the Brazilian Government is being inefficient in executing and elaborating public policies towards the refugees protection, on the other hand it reveals it self-conscious of its limitations, since it has been creating new institutional spaces. Nonetheless, still has to abandon the paternalistic view, which makes refugees passive recipients, transforming them in protagonists, reversing the current logic. That way, the State makes an evident mistake when not interfering with propper mechanisms and tools so the refugees can be able to study, qualify and integrate themselves to the labor market. The same way, the UNHCR can provide a more assertive participation within local integration. Thus, rethink the resettlement and local integration of refugees in Brazil goes essentially through overcoming institutional limits and inclusion barriers in current public policies